2021
DOI: 10.1001/jamanetworkopen.2021.8803
|View full text |Cite
|
Sign up to set email alerts
|

Association of Cigarette Type Initially Smoked With Suicidal Behaviors Among Adolescents in Korea From 2015 to 2018

Abstract: IMPORTANCE Assessment of whether past electronic cigarette (e-cigarette) use or initiating smoking with e-cigarettes is associated with suicidal behaviors among adolescents is needed to inform future research and public health interventions. OBJECTIVE To evaluate the association between starting smoking with e-cigarettes or conventional cigarettes and suicidal behaviors among Korean adolescents. DESIGN, SETTING, AND PARTICIPANTS This cross-sectional study analyzed data on adolescents in grades 7 through 12 who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…Our research is meaningful because we additionally analyzed the balance of sleep duration between weekdays and weekends using a “weekend CUS ratio.” Overall, our findings serve as a warning regarding the risk of depression or suicidal behaviors in adolescents with an imbalance of sleep duration between weekdays and weekends, and this is an important hypothesis to be confirmed in future neurobiological studies. Furthermore, because this cross-sectional study used multiyear national survey data (2015–2019) with 270,619 respondents based on random cluster sampling, our results were sufficiently representative of South Korean adolescents 30 , 49 . Additionally, we considered many covariates to increase the credibility and accuracy of our study.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Our research is meaningful because we additionally analyzed the balance of sleep duration between weekdays and weekends using a “weekend CUS ratio.” Overall, our findings serve as a warning regarding the risk of depression or suicidal behaviors in adolescents with an imbalance of sleep duration between weekdays and weekends, and this is an important hypothesis to be confirmed in future neurobiological studies. Furthermore, because this cross-sectional study used multiyear national survey data (2015–2019) with 270,619 respondents based on random cluster sampling, our results were sufficiently representative of South Korean adolescents 30 , 49 . Additionally, we considered many covariates to increase the credibility and accuracy of our study.…”
Section: Discussionmentioning
confidence: 96%
“…When the weekend CUS ratio was < 1.00, male and female adolescents living with relatives or with low perceived stress levels were more likely to experience depressive symptoms and suicidal ideation. Previous studies reported that adolescents living apart from one or both biological parents showed association with suicidality 30 , 42 . However, to the best of our knowledge, no study has investigated the association between mental health and sleep duration, especially weekend CUS, among adolescents living with relatives.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Despite these limitations, this study identified the effect of both the household type and of the individuals adolescents were living with and where they were living on the frequency of fast-food intake. Furthermore, the multiyear national survey data (2017–2020) were obtained from approximately 186,000 adolescents based on random cluster sampling, ensuring that the results were sufficiently representative of Korean adolescents [ 32 ].…”
Section: Discussionmentioning
confidence: 99%